Discussant of the paper: "The influence of CEOs in Shaping a Firm´s Sustainability Reporting and its Related Effect on Cost of Equiy Capital" - Lopes, A.I. (XVI Congresso de Contabilidade e Auditoria, 2017)
Discusant do paper "The influence of CEOs in Shaping a Firm´s Sustainability Reporting and its Related Effect on Cost of Equiy Capital"